The Relationship between the Headmaster's Innovation, the Completeness of School Infrastructure, and the Motivation with the Teachers' Performance - Ade Safitri (Universitas Negeri Malang, 2015)
Hubungan antara Inovasi Kepala Sekolah, Kelengkapan Sarana Prasarana Sekolah, Motivasi Kerja dengan Kinerja Guru SMA Abstract: This research aims to determine the relationship between the headmaster innovation (KS), the completeness of school infrastructure, and motivation to work with teacher performance. This study uses a quantitative approach design. The population of all the State High School teacher in Sumbawa Besar and sampling using proportionally. Analysis of the data using path analysis. The results of this study are: there is a direct relationship between the KS and teacher performance innovation, there is a direct relationship between innovation KS with work motivation of teachers, there is a direct relationship between the completeness of the infrastructure with the performance of teachers, there is a direct relationship between the completeness of the infrastructure work motivation of teachers, there is direct relationship between work motivation with teacher performance, there is a direct relationship between innovation KS, completeness school infrastructure, work motivation, teacher performance, there is no direct relationship between innovation KS, work motivation, teacher performance, there is no direct relationship between the completeness of the facilities school infrastructure, work motivation, with teacher performance. Key Words: innovation, principals, school infrastructure, work motivation, teacher performance   Abstrak: Penelitian ini bertujuan  untuk mengetahui hubungan antara inovasi kepala sekolah (KS), kelengkapan sarana prasarana sekolah, dan motivasi kerja dengan kinerja guru. Penelitian ini menggunakan rancangan pendekatan kuantitatif. Populasinya semua guru SMA Negeri di Kabupaten Sumbawa Besar dan pengambilan sampel menggunakan teknik secara proporsional. Analisis data menggunakan analisis jalur. Hasil penelitian ini adalah: terdapat hubungan langsung antara inovasi KS dengan kinerja guru, terdapat hubungan langsung antara inovasi KS dengan motivasi kerja guru, terdapat hubungan langsung antara kelengkapan sarana prasarana dengan kinerja guru, terdapat hubungan langsung antara kelengkapan sarana prasarana dengan motivasi kerja guru, terdapat hubungan langsung antara motivasi kerja dengan kinerja guru, terdapat hubungan langsung antara inovasi KS, kelengkapan sarana prasarana sekolah, motivasi kerja, dengan kinerja guru, terdapat hubungan tidak langsung antara inovasi KS, motivasi kerja, dengan kinerja guru, terdapat hubungan tidak langsung antara kelengkapan sarana prasarana sekolah, motivasi kerja, dengan kinerja guru. Kata kunci: inovasi, kepala sekolah, sarana prasarana sekolah, motivasi kerja, kinerja guru